Metagenome Analysis of a Complex Community Reveals the Metabolic Blueprint of Anammox Bacterium “Candidatus Jettenia asiatica” - Hu, Ziye; Speth, Daan R.; Francoijs, Kees-Jan; Quan, Zhe-Xue; Jetten, Mike (Frontiers in Microbiology, 2012)
Anaerobic ammonium-oxidizing (anammox) bacteria are key players in the global nitrogen cycle and responsible for significant global nitrogen loss. Moreover, the anammox process is widely implemented for nitrogen removal from wastewaters as a cost-effective and environment-friendly alternative to conventional nitrification-denitrification systems. Currently, five genera of anammox bacteria have been identified, together forming a deep-branching order in the Planctomycetes-Verrucomicrobium-Chlamydiae superphylum. Members of all genera have been detected in wastewater treatment plants and have been enriched in lab-scale bioreactors, but genome information is not yet available for all genera. Here we report the metagenomic analysis of a granular sludge anammox reactor dominated (∼50%) by “Candidatus Jettenia asiatica.” The metagenome was sequenced using both Illumina and 454 pyrosequencing. After de novo assembly 37,432 contigs with an average length of 571 nt were obtained. The contigs were then analyzed by BLASTx searches against the protein sequences of “Candidatus Kuenenia stuttgartiensis” and a set of 25 genes essential in anammox metabolism were detected. Additionally all reads were mapped to the genome of an anammox strain KSU-1 and de novo assembly was performed again using the reads that could be mapped on KSU-1. Using this approach, a gene encoding copper-containing nitrite reductase NirK was identified in the genome, instead of cytochrome cd1-type nitrite reductase (NirS, present in “Ca. Kuenenia stuttgartiensis” and “Ca. Scalindua profunda”). Finally, the community composition was investigated through MetaCluster analysis, 16S rRNA gene analysis and read mapping, which showed the presence of other important community members such as aerobic ammonia-oxidizing bacteria, methanogens, and the denitrifying methanotroph “Ca. Methylomirabilis oxyfera”, indicating a possible active methane and nitrogen cycle in the bioreactor under the prevailing operational conditions.